The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1364/ao.43.002561
|View full text |Cite
|
Sign up to set email alerts
|

Efficient mode transformations of degenerate Laguerre-Gaussian beams

Abstract: We present an approach for efficient conversion of a single-high-order-mode distribution from a laser to a nearly Gaussian distribution and vice versa. It is based on dividing the high-order mode distribution into equal parts that are then combined together coherently. We implement our approach with several optical arrangements that include a combination of discrete elements and some with single interferometric elements. These arrangements are analyzed and experimentally evaluated for converting the TEM01 mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…We check this approximation at a = 0 and note that it indeed reduces to the product of asymptotic approximations for the usual Airy functions, in which case expression (8) is also purely real.…”
Section: Mathematical Derivation Of the Relation ν (β )mentioning
confidence: 99%
See 1 more Smart Citation
“…We check this approximation at a = 0 and note that it indeed reduces to the product of asymptotic approximations for the usual Airy functions, in which case expression (8) is also purely real.…”
Section: Mathematical Derivation Of the Relation ν (β )mentioning
confidence: 99%
“…In their 1991 article [7] Abramochkin and Volostnikov discussed the mathematics of beam transformations under astig-matic conditions. Since then, different authors proposed and demonstrated mode conversion in lasers [8], linear and nonlinear optics [9,10] and free-electron beams in TEM [11]. In the latter work, Schattschneider et.…”
mentioning
confidence: 99%
“…The "starred" * beams remain propagation-invariant during free-space propagation, and their intra-cavity formation based on two coexisting laser modes has been explored in the past [26][27][28]. Figure 3 shows the formation of the "starred" field distribution for , * based on the superposition of the respective even , and odd , Laguerre-Gaussian beams [29].…”
Section: Formation Of Bessel Beams With Refractive Axiconsmentioning
confidence: 99%
“…Actually, the wavefront correction of a static single HOM has been demonstrated by using the binary phase plate [13][14][15][16] or the interferometric element [17]. However, these rigid devices are not capable to correct the dynamic wavefront of the beam with more than one HOM.…”
Section: Introductionmentioning
confidence: 99%